Durable Response and Good Tolerance to the Triple Combination of Toripalimab, Gemcitabine, and Nab-Paclitaxel in a Patient With Metastatic Pancreatic Ductal Adenocarcinoma - Shui, Lin; Cheng, Ke; Li, Xiaofen; Shui, Pixian; Li, Shuangshuang; Peng, Yang; Li, Jian; Guo, Fengzhu; Yi, Cheng; Cao, Dan (Frontiers in Immunology, 2020)
Abstract Background: The efficacy of Immune checkpoint inhibitors (ICIs) monotherapy were proved to be disappointing in pancreatic ductal adenocarcinoma (PDAC). Increasing evidence have shown that the promising efficacy of ICIs combined with systemic therapy in the first-line treatment in solid tumor. Case presentation: We reported a case of metastatic PDAC patient who was detected with PD-L1 positive expression in liver tumors and had a long-term partial response and good tolerance to the combined approach of toripalimab (a novel PD-1 inhibitor) and gemcitabine plus nab-paclitaxel (GA). In addition, we described the phenomenon of pseudo-progression of this patients during the course of therapy. Conclusion: For treatment-naïve metastatic PAC patients, GA plus toripalimab may provide a novel therapeutic approach with favorable response and manageable safety. Further clinical trials are needed to confirm the results. Pseudo-progression required specific attention and discrimination from true progression in patients undergoing immunotherapy.